DECADENCE DESCRIPTION OF THE LEXICON UNDERSTANDING IN THE PART OF THE BATAK TOBA’S BODY LANGUAGE BY TEENAGERS IN BATAM CITY - Dairi Sapta Rindu Simanjuntak; Yessie Aldriani (Universitas Putera Batam, 2019)
Indonesia is known as the country